Survey of Public Interest To Conduct Sports Activities At Pakansari Cibinong Stadion Bogor Post Pandemi Covid 19 - Sipahutar, Morel Sangge; M. Arief Setiawan; Dany Aulia (Jurnal Pendidikan Jasmani (JPJ), 2023)
Sport is a worldwide phenomenon and become an integral part of life for people on this earth. Sports on basically has a very strategic role for creation and improvement quality human resources for development. A city, county or province that wants rapid progress in various fields, even should not may merely be sloganistically assume sport as something important. This research aims toidentify how people's interest in carrying out sports activities at the Pakansari Cibinong Stadium, Bogor, uses a quantitative descriptive research method with a survey approach. Based on the research results, the level of public interest in carrying out sports activities at Pakansari Cibinong Stadium, Bogor, post the Covid 19 Pandemic, is included in the low category of 1% and high category of 99%. Based on the results of the research above, the researcher can convey the results of the research that has been carried out, related to the level of public interest in carrying out sports activities at the Pakansari Cibinong Bogor Stadium after the Covid 19 Pandemic with an average consideration of 100 respondents of 54.74%.